Performance of paddy crop in swampland under organic pellet fertilization from Azolla and vermicompost - Agus Hermawan; Dwi Probowati Sulistyani; Bakri (Jurnal Ilmiah Pertanian, 2021)
This study aimed to examine the effect of applying organic pellet fertilizers from vermicompost and Azolla using coal fly ash as an adhesive on paddy crop response in swampland. The research was performed in a pot experiment using a completely randomized factorial design with two treatment factors. The organic pellet fertilizer doses were: 0 ton ha-1 (a control); 10 ton ha-1; 20 ton ha-1; and 30 ton ha-1 as the first factor. In the second factor, the different NPK fertilizer dose was applied: the absence of NPK fertilizer as a control; 0.5 and 1 time of the recommended dose. The results showed that the application of organic pellet fertilizer significantly improved soil pH but not significant on soil organic C and N levels. There was tendency of increased on soil pH, C-organic, and N-total with the increased doses of organic pellet fertilizers applied. The NPK fertilizer application significantly improved plant height, tiller number and plant biomass as the dose were rised up. The organic pellet fertilizer application significantly improved plant height, number of tillers, and plant biomass. Applying organic pellet fertilizer at a dose of 10 tons ha-1 should be sufficient as no further improvement with the increasing doses.